2008
DOI: 10.2337/db07-0924
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Cardiomyocyte and Macrophage Peroxisome Proliferator–Activated Receptor γ in Cardiac Fibrosis

Abstract: OBJECTIVE— Cardiac fibrosis is an important component of diabetic cardiomyopathy. Peroxisome proliferator–activated receptor γ (PPARγ) ligands repress proinflammatory gene expression, including that of osteopontin, a known contributor to the development of myocardial fibrosis. We thus investigated the hypothesis that PPARγ ligands could attenuate cardiac fibrosis. RESEARCH DESIGN AND METHODS— Wild-type cardiomyocyte- and macrophage-specific PPARγ −/− mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 49 publications
4
54
1
1
Order By: Relevance
“…Treatment with simvastatin prevented the cardiac hypertrophy and fibrosis with a significant increase in the mRNA and protein levels of PPAR alpha and PPAR gamma at 32 weeks and 40 weeks. The results are in accordance with the effects of statins for the prevention of cardiac hypertrophy by activating the PPAR pathway and reducing the generation of reactive oxygen species [8,9] . PPAR alpha, the predominant PPAR isoform in the heart, has been implicated in hypertrophic signaling.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Treatment with simvastatin prevented the cardiac hypertrophy and fibrosis with a significant increase in the mRNA and protein levels of PPAR alpha and PPAR gamma at 32 weeks and 40 weeks. The results are in accordance with the effects of statins for the prevention of cardiac hypertrophy by activating the PPAR pathway and reducing the generation of reactive oxygen species [8,9] . PPAR alpha, the predominant PPAR isoform in the heart, has been implicated in hypertrophic signaling.…”
Section: Discussionsupporting
confidence: 85%
“…The expression of PPAR alpha is significantly diminished during pressure overloadinduced hypertrophy. In addition, cardiomyocyte-specific PPAR gamma deficiency has been reported to promote cardiac hypertrophy [9] . Several biochemical changes take place in the heart during interstitial fibrosis, including changes in the levels of matrix metalloproteinases (MMPs) [10] and the lysosomal cysteine protease, cathepsin S (Cat S) [11] .…”
Section: Introductionmentioning
confidence: 99%
“…29) Likewise, PPARγ ligands have been reported to attenuate AngII-induced cardiac fibrosis. 30) The pathological findings of this study also showed that treated mice had a lower level of fibrosis. Further studies should therefore aim to determine whether this decrease is due to the slight activation of PPARγ or the activation of PPARα.…”
Section: Discussionsupporting
confidence: 61%
“…Yao et al 11 were the first to report that PPAR-g agonists could reduce myocardial fibrosis in diabetic rats. Caglayan et al 12 reported that PPAR-g agonists attenuate angiotensin II-induced cardiac fibrosis by inhibiting myocardial macrophage infiltration. However, little is known about the role of rosiglitazone in cardiac remodeling evoked by essential hypertension.…”
Section: Discussionmentioning
confidence: 99%